THE EFFECT OF INSECT FRASS FERTILIZER APPLICATION ON THE PRODUCTIVITY OF BABY KAILAN (BRASSICA OLERACEA VAR. ALBOGLABRA) CULTIVATED PLANTS IN POLYBAGS USING SOIL AND RICE HUSK CHARCOAL AS GROWING MEDIA - Nur Paramita Dewi, Anisa
One way to overcome the problem of limited land and the abundance of organic waste is to develop urban farming with processed organic waste fertilizers, such as kasgot fertilizer. Urban farming on a household scale has considerable potential to improve food security in urban areas. One form of urban farming that can be applied on a household scale is by using a grow kit as a container. One factor that greatly influences the success of a grow kit is the composition of the growing media used. This study was conducted with the aim of determining the effect of the percentage of insect frass fertilizer on planting media and determining the best treatment for the growth and productivity of baby kailan (Brassica oleracea var. Alboglabra) plants. This research was conducted from January to March 2023 at Puri Indah, Jatinangor, and also at ITB Jatinangor Campus. This study consisted of a set of experiments using a completely randomized design (CRD) with 1 factor, namely the percentage of insect frass fertilizer in the planting medium. This study has 3 types of controls, namely negative control (K0), NPK positive control (K1), and compost positive control (K2), and has 3 insect frass fertilizer treatments at different percentages, namely 5% insect frass fertilizer (K3), 7.5% insect frass fertilizer (K4), and 10% insect frass fertilizer (K5). The research data were analyzed using the analysis of variance (ANOVA) method and significantly different results were further tested using the Tukey method at the 5% level. Based on this study, it can be determined that the difference in treatment does not give a significant difference to the number of leaves parameter. However, the difference in treatment gives a positive real difference to plant height, leaf area, wet weight, dry weight, plant moisture content, crown-root ratio, and plant productivity. From this study, it can also be concluded that the best treatment for baby kailan plant productivity is the K4 treatment or the combination treatment of soil, husk charcoal, and 7.5% insect frass fertilizer, and this treatment has better productivity results when compared to the positive control, namely NPK fertilizer and compost.